Thematic Structure of Students’ Anecdote Text - Mahriyuni; Tengku Silvana Sinar; T. Thyrhaya Zein; Nurhaliza (Jurnal Pedagogi dan Pembelajaran, 2023)
The thematic structure (theme-rheme) is the starting point of the message and develops. A text cannot be separated from a clause, making it a complete text. The purpose of this research is to determine the theme used in student anecdotal texts depending on the level of achievement determined by the score. This type of research is qualitative. These students come from class A and are taking the second semester. Of the 15 texts selected for the exam, they have been divided into three categories based on their level of attainment. Methods of data collection using documentation. This study uses the data analysis method proposed by Krippendorff. Based on the findings of this study, the themes that appeared the most were Topical themes, which appeared 139 times (63%), and Textual themes, which appeared 67 times (31%). And Interpersonal themes appeared 14 times (6%). At the moderate level, the theme that appeared the most was the topical theme which appeared 119 times, followed by the textual theme with 46 occurrences, and the interpersonal theme with 11. At the lowest level, the topical theme appeared the most, with 87 occurrences (67%), followed by textual themes (34 occurrences (26%), and interpersonal themes (9 occurrences (7%). At a high level, dual themes became the dominant theme appearing 85 times (61%), while simple themes appeared 54 times (39%). At the medium level, the simple theme is more dominant than the double theme at the low level, with 46 occurrences (53%), while the dual theme has 41 occurrences (46%).